Atrial reverse remodeling represented by the atrial conduction time in persistent atrial fibrillation patients after catheter ablation: its impact on predicting late atrial fibrillation recurrence. Issue 5 (May 2020) - Hori, Yuichi; Nakahara, Shiro; Fukuda, Reiko; Sato, Hirotsugu; Ukaji, Tomoaki; Koshikawa, Yuri; Nishiyama, Naoki; Ishikawa, Tetsuya; Kobayashi, Sayuki; Taguchi, Isao
Highlights: Atrial conduction time to left atrial appendage (P-LAA TDI) was measured by transthoracic echocardiography. P-LAA TDI exhibited a significant reduction by 6 months after persistent atrial fibrillation (AF) ablation. Late AF recurrence was related to P-LAA TDI after the reverse remodeling of atrium. Abstract: Background: The aim of this study was to examine the reduction in the atrial conduction time during the follow-up phase of catheter ablation in persistent atrial fibrillation (PsAF) patients, which would suggest atrial reverse remodeling, and to investigate its impact on predicting AF recurrence. Methods: Fifty-seven PsAF patients underwent radiofrequency catheter ablation. The P-wave to left atrial appendage (LAA) conduction time was measured by transthoracic echocardiography using tissue Doppler imaging (P-LAA TDI), within 24 h and 6 months after ablation. Results: The accuracy of the P-LAA TDI was confirmed by measuring the actual electrophysiological data during the ablation (90 ± 13 ms, r = 0.754, p  < 0.001). The P-LAA TDI was significantly reduced (170 ± 18 msec to 159 ± 19 msec, p  < 0.001) at the 6-month follow-up. Sixteen patients (28%) had an AF recurrence by 12 months of follow-up. The no-AF recurrence group had a significantly reduced P-LAA TDI 6 months later (165 ± 15 msec to 155 ± 18 msec, p  < 0.001), while there was no significance in the AF recurrence group (184 ± 21 msec to 174 ± 16 msec, p  = 0.091). The P-LAA TDI was a predictive factor of AF recurrence after ablation with a cut-off value of >175 msec (sensitivity = 0.750, specificity = 0.780) when measured within 24 h after ablation and >166 msec (sensitivity = 0.750, specificity = 0.756) when calculated at 6 months of follow-up. Conclusions: In PsAF patients, a significant reduction in the P-LAA TDI was observed at 6 months of follow-up, which may have represented the occurrence of left atrial reverse remodeling. These findings suggested that the P-LAA TDI time in the follow-up was appropriate for predicting late AF recurrences.